A Prediction of The Air Quality Index: An Analysis of Ghaziabad City - Kumar, Lokesh; Kumar, Gaurav (International Journal of Engineering and Management Research, 2025)
PM10 is one of the main air pollutants that causes air pollution. This study used Artificial Neural Networks (ANN), a common learning technique, to estimate the impact of this contaminant on human health and the environment using data between 2019 and 2023. The Pollution Control Board of Uttar Pradesh (UPPCB)'S air observation center obtained information related to the center of industry of Ghaziabad and finished the simulation and optimization procedures required using SPSS programming. Before being compared with the real data, the obtained air quality estimation results underwent a multilayer perceptron analysis. Moreover, there have been instances where the Ghaziabad province's Air Quality Index (AQI) values have exceeded the allowable limit, especially during times of great output.